(3QSGdI GdUMGHIs - (3Ydj Hf eMeO Hf GdYHGS GdJhMjOj, CHh MjGf,J (B400 (3g` s
(3ChdgG (B:s
(3QSGdI dCHi MjGf GdJhMjOi Yf CHj HcQ hYdi s
(3Ydi dSGf CHj HcQ GdUOjb QVi Gddg Yfg Edi Ydi Hf CHj WGdH QVi Gddg Yfg hHBNQgG TQM ddCdaGX GdZQjHI ajgGs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B4 - (3U (B326 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B7 - (3U (B205 ; (3gOjI GdYGQajf ddHZOGOi(B: (3L (B1 - (3U (B684s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B1 - (3bSe (B5 - (3U (B126 s
(3eUOQ GbJfGA GdCUd (B:s
(3ESchQjGd (B(1/538) s
Keywords: (3GdJhMjO hGdedd hGdfMds